2014
DOI: 10.1017/s0032247414000151
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous climatic conditions during winter 2010–2011 and vulnerability of the traditional Inuit food system in Iqaluit, Nunavut

Abstract: This study examines how climatic extremes during winter 2010–2011 affected the traditional food system in Iqaluit, Nunavut. This winter was anomalous throughout the Canadian Arctic, and manifested itself locally by warmer temperatures and decreased ice coverage. Drawing upon in-depth interviews with hunters (n = 25), a fixed question survey with public housing residents (n = 100), as well as analysis of remotely sensed sea-ice charts and temperature data from the Iqaluit weather station, this work identifies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 86 publications
(111 reference statements)
1
10
0
Order By: Relevance
“…Notably, the seasonal experience of FI was not homogeneous, differing in magnitude based on household livelihood strategy and engagement in subsistence agriculture. These findings are consistent with the body of research on the impact of seasonal variation on subsistence and Indigenous populations globally and within Uganda; that is, social determinants of health mediate seasonal impacts ( 14 , 18 , 40 , 47 ) . These results have implications for our ability to generalize trends in climate change vulnerability even within small areas and across seemingly homogeneous sub-populations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Notably, the seasonal experience of FI was not homogeneous, differing in magnitude based on household livelihood strategy and engagement in subsistence agriculture. These findings are consistent with the body of research on the impact of seasonal variation on subsistence and Indigenous populations globally and within Uganda; that is, social determinants of health mediate seasonal impacts ( 14 , 18 , 40 , 47 ) . These results have implications for our ability to generalize trends in climate change vulnerability even within small areas and across seemingly homogeneous sub-populations.…”
Section: Discussionsupporting
confidence: 89%
“…Such proxies provide a lens through which the role of climatic factors in affecting food systems can be characterized, providing a basis for understanding the potential implications of future change. This approach is referred to in the literature as a ‘temporal analogue’ and is frequently used in climate change vulnerability research ( 34 , 35 , 40 ) . Here, we used a longitudinal study design to provide multiple measures from each season, as shorter-term studies can be skewed by conditions during the study period and may not demonstrate longer-term trends ( 13 ) .…”
Section: Methodsmentioning
confidence: 99%
“…Many rural and remote regions have expe rienced changing access to, and quality of, food and water systems, linked to environmental changes such as rising temperatures, 7,16,20,23 changing precipita tion patterns, and increasing incidents of extreme weather events. 7,18,23 For example, in many Northern remote First Nations and Inuit communities, climatechange related disruptions to sea ice, wildlife, and vegetation impacts the ability of individu als to hunt, fish, and forage, leading to decreased consumption of healthy and culturallypreferred local food and increased reliance on retail food.…”
Section: Changing Access and Availability Of Nourishing Accessible mentioning
confidence: 99%
“…Other research has shown the damaging effects of later freeze-up on the subsistence food harvest (Statham et al, 2015). Discussions with residents suggest that the longer the freeze-up remains dynamic and susceptible to autumn storm effects, the harder it can be to transit the upper foreshore and beach (T. Tremblay, CNGO, pers.…”
Section: Discussionmentioning
confidence: 99%